Day 2 Tue, April 04, 2017 2017
DOI: 10.2118/184572-ms
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Filter Cake Generated by Nanoparticle-Based Drilling Fluid for HP/HT Applications

Abstract: As high-pressure/high-temperature (HP/HT) drilling is inherently expensive, drilling fluids and technologies should be carefully selected to successfully handle the associated challenges. Over the past few years, nanoparticles (NPs), among other additives, have been investigated to address these challenges. The objective of this study is to investigate the potential of using ferric oxide NPs on the filter cake properties in downhle drilling environments. Having an efficient filter cake is an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…At the concentration of 0.5 wt %, a smoother filter cake morphology with less agglomeration was observed from SEM images. The filter cakes were further examined with Computed-Tomography (CT) scans and SEM analysis and the results were reported in another study [15]. The authors concluded that addition of Fe 2 O 3 NP to the drilling fluids improved the filter cake characteristics under both static and dynamic filtration conditions.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…At the concentration of 0.5 wt %, a smoother filter cake morphology with less agglomeration was observed from SEM images. The filter cakes were further examined with Computed-Tomography (CT) scans and SEM analysis and the results were reported in another study [15]. The authors concluded that addition of Fe 2 O 3 NP to the drilling fluids improved the filter cake characteristics under both static and dynamic filtration conditions.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…By comparing the curves before and after adding nanoparticles, it could be seen that the filtration volume decreases by increasing nanoparticles. There is also a range that nanoparticles could do their best in lowering the filtration volume that is stated in the literature (Mahmoud et al 2017). The relative deviation that measures the difference between predicted and actual data gives an illustrative view about the adjacency of actual and model target.…”
Section: Resultsmentioning
confidence: 99%
“…The utilized nanoparticles and their respective studies that are contributed in the data bank are SiO 2 (Parizad et al 2018), Fe 2 O 3 (Vryzas et al 2015;Mahmoud et al 2017 . The experimental data in these studies have included the impact of nanoparticle type, nanoparticle concentration (wt%), KCl salt concentration (wt%), temperature (°F), pressure (psi), RPM (round/min), and time (s) on filtration volume (ml) of water-based drilling fluid.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations